MOISTURE DISTRIBUTION DURING THE COTTON RAW MATERIAL DRYING PROCESS (Neo Science Peer Reviewed Journal, 2024)
In modern technologies, which are currently used in this article,the moisture content of cotton in the drying process is of greatimportance. At this point in the drying process, scientific research on the distribution of its moisture, the results of which arereflected.